Exploration of pedagogic competence of teacher professional education students towards the culturally responsive teaching - Siti Nurbaya; Mei Anjar Kumalasari; Khairanisa Hening Pratiwi (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
This study seeks to systematically evaluate the cognitive academic competence of pre-service teachers within professional education programmes concerning the Culturally Responsive Teaching (CRT) framework. Employing a quantitative survey methodology, the research involved a cohort of 140 students enrolled in the Indonesian Language and Literature teacher professional education programme across four higher education institutions (Yogyakarta State University, Ahmad Dahlan University, Sarjanawiyata Tamansiswa University, and Sanata Dharma University) during the 2023–2024 academic year. Data were gathered utilising a structured four-option multiple-choice instrument. The findings reveal a disparate spectrum of cognitive comprehension amongst the participants regarding the CRT approach. Specifically, the pre-service teachers demonstrated commendable proficiency in understanding the definition, benefits, and underlying principles of CRT. Furthermore, their understanding of the framework's purpose, core components, and distinct characteristics was deemed adequate. However, a significant deficiency was identified in their foundational knowledge; their understanding of both the philosophical underpinnings and the historical background of the CRT approach was categorised as poor. Ultimately, these results delineate specific areas requiring pedagogical intervention to ensure comprehensive mastery of CRT amongst future educators.